POLYOXOMETALATES: A NEW CLASS OF STAINING AGENTS - Milosavljević, Aleksandra (Medicinski podmladak, 2024)
For decades, transmission electron microscopy (TEM) has been one of the most valuable methods for analysing the ultrastructure of biological specimens, especially in the research field of medicine. Samples for TEM need quality preparation to obtain a contrast that can be detected in electron micrographs. Substances that make it possible to achieve a quality contrast in TEM are salts of heavy metals. One of the most successful substances for achieving contrast in TEM is uranyl acetate (UAc), because of very detectable contrast properties. Nevertheless, the latest change in regulations about radioactivity of materials gravely prohibits the use of UAc, although it would be applied exclusively for scientific reasons. Considering that UAc is dangerous because of both its toxicity and radioactivity, buildout of new secure substitute is essential. This is the present problem in TEM procedure which urges to be solved. The aim of this review is to show the probability of use of polyoxometalates (POMs) as new potential contrast reagents. POMs are heavy atoms sources with wide range of biological activities. Extensive chemical characterization of POMs brings promising use of these substances as new contrast agents for TEM observation of biological samples.
Keywords: transmission electron microscopy; polyoxometalates; uranyl acetate; contrast agents